PRACTICE OF EARLY REDUCED-ANTIGENIC-LOAD BCG-M VACCINATION OF HIV-EXPOSED INFANTS - S. N. Shugaeva; A. G. Petrova (LLC "Diagnostics and Vaccines", 2015)
A practice of an early reduced-antigenic-load BCG-M vaccination of HIV-exposed infants inIrkutskdistrict, a district with the high HIV and tuberculosis (TB) prevalence, had been evaluated. It had been establish that the vaccination within the conventional time frame leads to the development of an anti-tuberculous immune response which, usually, is verified by the post-immunization reactions and the tuberculosis skin test results. A high safety of the reduced-antigenic-load BCG-M vaccination had been confirmed in cases with perinatally HIV-infected infants. The clinical development of the TB infection in non-vaccinated children, especially of the youngest age, had been characterized by a development of the hazardous complications which tend to be persistent.